Physical, psychological, cognitive, social health outcomes, and health-related quality of life in out-of-hospital cardiac arrest survivors and their caregivers: Protocol of the quality cardiac arrest survivorship cohort study (QualiCAS) - Pin Pin Pek; Megan Chua; Le Xuan Liew; Christina Chen; Shir-Lynn Lim; Felix Maverick Rubillar Uy; Vui Kian Ho; Yew Woon Chia; Jia Min Chua; Ee Ling Goh; Lai Peng Tham; Pei Lin Koh; et al. (Resuscitation Plus)
Background: Out-of-hospital cardiac arrest (OHCA) is an emergency with historically low survival rates. Advances in resuscitation and post-resuscitation care have improved survival, precipitating greater scientific interest in OHCA patients’ survivorship. However, there is insufficient high-quality population-based long-term survivorship data and limited research on the impact of OHCA sequelae on survivors’ caregivers. Objective: Our primary aim is to determine neurological function, physical, psychological, cognitive, social outcomes, and health-related quality of life (HRQoL) of OHCA survivors in Singapore. Secondary aims are to quantify caregivers’ burden and its association with their HRQoL, and psychological well-being. Methods: The Quality Cardiac Arrest Survivorship Cohort Study (QualiCAS) is a prospective population-based cohort study of OHCA survivors and their caregivers in Singapore. Participants aged ≥18 years and caregivers aged ≥21 years will be recruited from all public hospitals in Singapore. Health outcomes will be evaluated at 3, 6, and 12 months, and 3 and 5 years using the Hospital Anxiety and Depression Scale, PTSD Checklist for DSM-5, Fatigue Severity Scale, Montreal Cognitive Assessment Tool, EQ-5D-5L, Community Integration Questionnaire-Revised, Barthel Index, Lawton’s Instrumental Activities of Daily Living, Timed Up and Go Test, Handgrip strength assessment, and Zarit Burden Interview. Discussion: This study allows us to understand the natural history of OHCA survivorship and quantify the burdens on patients and their caregivers. Findings can guide clinical follow-up, identify high-risk patients, intervention targets, and inform rehabilitation strategies for OHCA sequelae.